Counseling and demonstration of the use of medicinal plants in the South Bambu sub-district, West Jakarta: Penyuluhan dan demo pemanfaatan tanaman obat di wilayah kelurahan bambu selatan Jakarta barat - Yulis Adriana; Febri Hidayat; Dede Komarudin; Dewi Rahma Fitri (Lembaga Publikasi Ilmiah Nusantara, 2026)
The community service program that has been implemented by the Pharmacy study program of the Al Kamal Institute of Science and Technology regarding counseling and demonstrations on the use of medicinal plants to improve public health in the South Bambu sub-district, West Jakarta. Counseling and demonstrations on the use of medicinal plants are educational activities to introduce, teach how to process, and demonstrate the use of medicinal plants for health. This activity includes providing material on the benefits of medicinal plants, how to process them such as boiling or mixing, as well as direct demonstrations on making simple potions and cultivation. The purpose of this activity is to increase the knowledge and skills of the community so that they can utilize medicinal plants as an alternative natural treatment to maintain daily health. This counseling and demonstration was carried out at the Bambu Kuning Child-Friendly Integrated Public Space (RPTRA). The Bambu Kuning Child-Friendly Integrated Public Space (RPTRA) is one of the places in the South Bambu City Village, Palmerah District, West Jakarta. The facilities in the RPTRA are not only child-friendly, but also disabled-friendly. In addition, there are many types of TOGA plants planted by the administrators in the Bambu Kuning RPTRA area. Counseling activities on the use of medicinal plants and demonstrations on making juice mixed with single garlic, lemon juice, ginger juice, apple cider vinegar and honey as well as making healthy drinks from aloe vera plants. This activity received a very good response from the local community with many questions about the use of medicinal plants to support public health